Three-Dimensional Accuracy of Printed Alveolar Casts - Alghamdi, Mohanned. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Posthodontics.; Advisor: Panos Papaspyridakos.; Committee: Aikaterini Papathanasiou, Matthew Finkelman, Yo-Wei Chen, and Yukio Kudara.; Keyword: Dentistry.